A STUDY OF BEHAVIORAL INTENTION OF UNDERGRADUATES TOWARDS THE USAGE OF E- LEARNING SYSTEMS - Gweneth Kok Yi Wen,; Eunice Chong Jia Ern,; Khoo Xin Qi,; Cynthia Sim,; Yap Jia Jun,; Teh Su Yen, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The quick and wide usage of e-learning in Malaysia was pushed by the spread of the Covid-19 pandemic and the Movement Control Order (MCO). The e-learning systems were put in place to ensure students of all education levels would not face any disruptions in their studies. This indicated a significant shift in teaching and learning in Malaysia, from primary to tertiary education. Therefore, this research investigates the behavioural intention of 381 undergraduates in using the e-learning systems subscribed by the university. By using the UTAUT Model as the theoretical framework, the research findings indicated significant relationships between Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Social Influence (SI), Internet Connectivity (IC), Technical Support (TS) and Behavioural Intention (BI) of the respondents in using e-learning systems. The results benefit the university and education industry and enable them to chart how teaching and learning can be executed as the country moves forward to the endemic phase.